2009
DOI: 10.1080/03601270902885504
|View full text |Cite
|
Sign up to set email alerts
|

Comprehension of Health-related Written Materials by Older Adults

Abstract: This study examined how Flesch Reading Ease and text cohesion affect older adults' comprehension of common health texts. All older adults benefited when high Flesh Reading Ease was combined with high cohesion. Older adults with small working memories had more difficulty understanding texts high in Flesch Reading Ease. Additionally, older adults with low verbal ability or older than 77 years of age had difficulty understanding texts high in text cohesion but low in Flesch Reading Ease. These results imply that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 40 publications
0
16
0
5
Order By: Relevance
“…However, others have found no difference in how much high-literacy individuals understood simplified materials or their original, hard-to-read versions (Davis et al, 2006;Pignone et al, 2005). Still others have found that simplified materials decreased comprehension among some high literate adults (Liu et al, 2009) due to the simplification having potentially introduced ambiguity and reduced the quality of the content.…”
Section: Introductionmentioning
confidence: 99%
“…However, others have found no difference in how much high-literacy individuals understood simplified materials or their original, hard-to-read versions (Davis et al, 2006;Pignone et al, 2005). Still others have found that simplified materials decreased comprehension among some high literate adults (Liu et al, 2009) due to the simplification having potentially introduced ambiguity and reduced the quality of the content.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, researchers have highlighted the importance of attending to a myriad of other design elements, in addition to readability (Doak, Doak, Friedell, & Meade, 1998;Seligman et al, 2007). These include text cohesion, organization, layout, graphics, writing style, cultural factors, and the amount of information presented (Doak, Doak, & Root, 1996;Liu, Kemper, & Bovaird, 2009;Meade & Smith, 1991). In addition, it is important to consider cognitive factors such as demands on working memory (Wilson & Wolf, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This refers to the use of explicit words, phrases, and sentences to guide the reader through the text and enhance comprehension by making connections between sentences, topics, and ideas (Liu, Kemper, & Bovaird, 2009 There is consensus that one should write in active voice because it improves readability and is more likely to move the reader to action compared to the same message written in passive voice (Centers for Disease Control and Prevention, 2009;National Cancer Institute, 2003;Vahabi & Ferris, 1995). It is also recommended to use short words that are familiar to the reader (one to two syllables where possible) and short sentences (8 to 10 words).…”
Section: Languagementioning
confidence: 99%
“…This is an objective measurement of the reading skills necessary to understand a written text and is typically measured in terms of grade level . Readability formulae are used to assess reading level and are based on language variables such as sentence length, word length, and syllable counts Liu, Kemper, & Bovaird, 2009;Vahabi & Ferris, 1995).…”
Section: Languagementioning
confidence: 99%
See 1 more Smart Citation